SOCIAL-PSYCHOLOGICAL INDICATORS OF PROVIDING GENDER EQUALITY IN FORMING THE RESERVE OF MANAGEMENT PERSONNEL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In modern research on the problem of identity, there are many attempts to clarify the issue of gender. First of all, this is related to the approaches related to socio-psychological changes in society, i.e. transformations in the norms, stereotypes, and social images of behavior in the relationship between men and women. It is also important to take into account socio-psychological factors in ensuring gender equality in the formation of personnel reserves, and the results of empirical research conducted on this issue are analyzed in the article.